Performance evaluation of China's high-tech innovation process: Analysis based on the innovation value chain. (June 2018) - Chen, Xiafei; Liu, Zhiying; Zhu, Qingyuan
Abstract: The Chinese high-tech industry has developed greatly since the beginning of China's "National High-tech R&D (863) Program" and "China Torch Program". This paper introduces a conceptual model extended from the innovation value chain model to simultaneously estimate the R&D and commercialization efficiencies for the high-tech industries of 29 provincial-level regions in China. To match reality, a network DEA incorporating both shared inputs and additional intermediate inputs is constructed to open the "black box" view of decision making units used in single-stage DEA. This study is the first attempt to link the R&D and commercialization with a solid theoretical foundation and feasible mathematical methods. The empirical findings show that most of the 29 regions have low efficiency in the commercialization sub-process compared to the R&D sub-process, although there are regional differences in China's high-tech industry. Pearson correlation shows that the R&D sub-process is not closely correlated to the commercialization sub-process in terms of efficiency. Our analysis can provide information for the formulation of policies to achieve high innovation efficiency. Highlights: It constructs a two-stage conceptual framework for performance evaluation under the innovation value chain theory. It gives insight into the appropriate proportion of shared resources in each sub-process. It analyzes the high-tech industry innovation activities from the perspective of the regional innovation system. It provides some policy implications and recommendations of China's high-tech innovation.